Impacts of psychological wellbeing with HIV/AIDS and cancer among sexual and gender minorities: A systematic review and meta-analysis - Chan, Alex Siu Wing; Leung, Lok Man; Li, Jane Siu Fan; Ho, Jacqueline Mei Chi; Tam, Hon Lon; Hsu, Wing Leung; Iu, April Nicole On Sang; Tang, Patrick Ming Kuen; Yan, Elsie (Frontiers in Public Health, 2022)
Background: The agony and economic strain of cancer and HIV/AIDS therapies severely impact patients’ psychological wellbeing. Meanwhile, sexual minorities experience discrimination and mental illness. LGBT individuals with cancer and HIV/AIDS play two roles. It is worthwhile examining this group’s mental wellbeing. Objective: The purpose of this study is to synthesize current studies on the impact of HIV/AIDS and cancer on LGBT patients’ psychological wellbeing. Methods: This research uses a systematic literature review at first and later stage a meta-analysis was run on the same review. In this study, data from Google academic and Web of Science will be used to filter literature. PRISMA 2020 Flow Diagram seeks research on LGBT cancer and HIV/AIDS patients. The above sites yielded 370 related papers, some of which were removed due to age or inaccuracy. Finally, meta-analyses were done on 27 HIV/AIDS and 34 cancer analyses. Results: The research included 9898 LGBT cancer sufferers with AIDS and 14465 cancer sufferers with HIV/AIDS. Using meta-analysis, we discovered the gap in psychological wellbeing scores between HIV/AIDS LGBT and non-LGBT groups ranged from -10.86 to 15.63. The overall score disparity between the HIV/AIDS LGBT and non-LGBT groups was 1.270 (95% CI =0.990-1.560, Z=86.58, P<0.1). The disparity in psychological wellbeing scores between cancer LGBT group and general group varies from -8.77 to 20.94 in the 34 papers examined in this study. Overall, the psychological wellbeing score disparity between the cancer LGBT subset and the general group was 12.48. (95% CI was 10.05-14.92, Test Z value was 268.40, P value was 0). Conclusion: Inflammation and fibrosis in HIV/AIDS and cancer sufferers adversely affect their psychological wellbeing.